A prática da leitura no 4º ano do ensino fundamental: análise na perspectiva de professores e alunos - PONTE, Luciana Moura (2020)
Reading practices in schools is a theoretical interest theme as Angela Kleiman (2000), Luiz Carlos Cagliari (1997), Paulo Freire (1988) Irandé Antunes (2003) among others, making it clear that it is relevant and it needs to be debated. Based on the theories of the above authors, this study examined the process that involves teaching reading in primary school and aimed to show how they are carried out the reading practices in three classes of the 4th year of elementary school. As a methodological option, we opted for a qualitative research method. Data collection instrument was used observations in the classroom, interviews with teachers and questionnaires given to students. For the analysis of the data was made the triangulation of information from the instruments used, allowing us to explain the factors that underpin the way reading is developed by a professor at the 4th year of elementary school. On the results, we note that in general the practice of reading done by the teachers was developed sporadically and without due attention to the practice. Reading was developed mechanized without context or meaning in/to the lives of students summing up to the fact copy the text to after doing the exercise. In this sense it becomes necessary to review the way that reading is developed in the classroom to teach students to like the act of reading, but that students need to like reading that they are in schools and, above all, it is valid the contextualization of the text read so that you can make pleasant reading, interesting, attractive, and that makes sense for those who are reading.